Study of the Cirebon Wayang Wong Performance Arts in Educational Value - Dadang Sunendar; Sumiyadi; Tedi Permadi; Fiki Setiawan; Taiman (PT Inovasi Pratama Internasional, 2023)
Wayang is a traditional art and an important cultural heritage. In addition to being recognized as a Javanese cultural heritage by UNESCO, wayang is a beautiful and significant Indonesian cultural heritage. Educational values in wayang wong in Cirebon society have been almost extinct. As a sense of pride as the Indonesian nation that will pass on cultural values as an embodiment of local wisdom (local wisdom), which can be used as a cultural inheritance repertoire for wayang wong in the future. The study and performance of values as a means of revitalizing the current generation through preservation and local knowledge to preserve noble values. Qualitative research (Qualitative research) is an investigation designed to describe and analyze individuals or groups. Several descriptions are employed to discover underlying principles and explanations that lead to conclusions. Therefore, students in the value of education through wayang Cirebon performing arts must apply values to education that apply to daily life.